Kualitas Hijauan Sorgum dan Legume Indigofera Berbentuk Silase Berdasarkan Karaktersitik Nutrisi Sebagai Pakan Ruminansia - Anwar Efendi Harahap; Arsyadi Ali; Bakhendri Solfan; Jepri Juliantoni; Fitri Harianti; Sherly Andini (Agriekstensia : Jurnal Penelitian Terapan Bidang Pertanian, 2024)
Sorghum and indigofera legumes are forage sources of energy and crude protein which can be combined into complete and inexpensive silage feed. This research aims to determine the quality of forage sorghum and indigofera legumes in the form of silage based on nutritional assessment. The research method used RAL with 4 treatments and 5 replications. The treatments used were S0 (100% sorghum), S1 (70% sorghum + 30% indigofera legumes), S2 (30% sorghum + 70% indigofera legumes) + S3 (100% indigofera legumes) with each treatment added with molasses, corn flour and rice bran. The results showed that the combination treatment of sorghum + indigofera legumes influenced (P<0.05) all nutritional parameters observed. indigofera) because it can increase dry matter, crude protein, BETN as well. The best combination was found in the S2 treatment (30% sorghum + 70% indigofera legume) because it was able to increase dry matter, crude protein, BETN and reduce the overall crude fiber content of the silage.